Mindfulness and Meditation: The Most Potential Influences to Improve Adolescent Mental Health in East Java (West Science Interdisciplinary Studies, 2023)
This research explores the potential influences of mindfulness and meditation practices on adolescent mental health in East Java, Indonesia. Adolescence is a critical period marked by significant physical and emotional changes, making mental health a growing concern. Mindfulness and meditation have gained recognition globally as tools for enhancing mental well-being, but their effectiveness in East Java’s cultural context remains underexplored. We employed a mixed-methods approach, combining quantitative 145 sample surveys and qualitative 5 informan interviews, to investigate this relationship comprehensively. The quantitative analysis revealed a statistically significant positive impact of mindfulness and meditation practices on mental health outcomes, with variations based on gender, age, and socio-economic status. Qualitative findings highlighted the cultural significance of these practices and the importance of community and family support. Despite the positive cultural attitudes, stigmatization of mental health issues remains a challenge. These results emphasize the need for culturally tailored interventions that integrate traditional values and address stigma, ultimately contributing to the well-being of East Javanese adolescents.